State of antioxidant system of rat thymocytes in experimental ulcerogenesis - V. A. Kovaleva; L. M. Gaida; A. E. Shevchenko; D. V. Shelest; L. I. Ostapchenko (The Ukrainian Biochemical Journal, 2014)
Features of free radical processes and their impact on the implementation of immunocompetent cells of their functions under conditions of peptic ulcer are insufficiently studied today. Reduced activity of catalase 1.7 and 3.4 times and that of glutathione peroxidise ~ 2.0 times, accordingly, were observed in both models of gastric ulceration (stress ulcer and ethanol one). Enzymatic activity of superoxide dismutase decreased 1.5 times and activity of glutathione transferase increased 1.8 times in the stress model in contrast to the ethanol model of stomach ulcer. Obtained results indicate the exhaustion of antioxidant system in rats’ thymocytes under experimental ulcerogenesis. These data confirm complex negative effect of ulcer on the organism.